2021
DOI: 10.1155/2021/7453500
|View full text |Cite
|
Sign up to set email alerts
|

COL3A1 and Its Related Molecules as Potential Biomarkers in the Development of Human Ewing’s Sarcoma

Abstract: Background. Ewing’s sarcoma (ES) is the most common malignant primary bone tumor in children and adolescents. This study is aimed at developing new prognostic markers and building a microRNA-mRNA network in the development of ES. Method. GSE80201 and GSE39262 were downloaded from the Gene Expression Omnibus (GEO) database. Bioinformatics analysis was used to download and process data. The coexpression of differentially expressed microRNAs (DEMs) and genes (DEGs) was selected by using R software. The FunRich da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Additionally, the oncogene SOX4 is prominently featured in our differential analysis of tumor cells (72). These genes are also identified as diagnostic or prognostic biomarkers in previous studies (70, 7376). Notably, some cell types also share similar gene expression patterns (Figure 6C).…”
Section: Resultsmentioning
confidence: 81%
“…Additionally, the oncogene SOX4 is prominently featured in our differential analysis of tumor cells (72). These genes are also identified as diagnostic or prognostic biomarkers in previous studies (70, 7376). Notably, some cell types also share similar gene expression patterns (Figure 6C).…”
Section: Resultsmentioning
confidence: 81%
“…COL3A1 encoded the polypeptide chain which was the building block of type III collagen. The expression of this gene has an essential role in the proliferation and migration of tumor cells and is dysregulated in several malignancies, such as ovarian cancer and brain tumor [ 58 , 59 ]. Collagen, type II, alpha 1 peptide encoded with COL2A1 form the homotrimer Type II collagen [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the COL1A2 gene was shown to be upregulated in ES tissues [ 40 ], and we also obtained consistent results in RD-ES cells. Zhang et al [ 41 ] found that COL1A2 was involved in the development of ES and was significantly associated with the survival time of ES patients. Our survival curves also suggest that patients with low COL1A2 expression have shorter survival times.…”
Section: Discussionmentioning
confidence: 99%